Cytotoxic effects of an acidic Ribosome-inactivating Protein like protein isolated from Mirabilis jalapa L. leaves on cancer cell-lines - ., Sudjadi; Witasari, Lucia D.; Sadarum, Modesta T.; Nastity, Nia; ., Sismindari (Indonesian Journal of Pharmacy, 2007)
Most purification approaches of Ribosome-inactivating Proteins (RIPs) used a cation exchange chromatography resulting highly basic proteins, such as MJ-30 isolated from Mirabilis jalapa leaves. The M.jalapa unbounded protein fractions of the column showed cleavage activity on supercoiled double stranded DNA and possesed cytotoxic effects on cancer cell lines. So the purification and characterization of the acidic protein was needed to be done.Total proteins of M.jalapa leaves was collected from precipitating process of the extract using ammonium sulphate untill saturated. After dialysis, the proteins was applied into the weak base anion exchanger Ionenaustaucher Typ II. The bounded proteins was eluted with 0.0 to 0.5 M NaCl gradient in phosphate buffer. Active protein fractions were determined by supercoilded DNA cleavage activity and then cytotoxic activity was testes.Results showed that protein fraction eluted at 0.35 – 0.40 M NaCl possesed cleavage activity on supercoiled DNA. The acidic protein, MJ-C, was toxic on HeLa, Myeloma and T47D cell lines, with the LC50 of 14.3 μg/mL, 7.4 μg/mL and 27.8 μg/mL, respectively. The MJ-C was more potent than the basic protein MJ-30.Key words: acidic RIP, cytotoxic, Mirabilis jalapa